«L’Erba voglio» (1971-1977): un gruppo di desiderio nella stagione dei movimenti - Monica Pacini (Laboratoire Italien)
The essay analyses the Milanese journal L’Erba voglio (1971-1977) in the context of the season of movements. It aims to reconstruct the network of cultural, political and personal relations which paved the way for its creation and circulation in 1970s Italy. Drawing on the biographies and writings of Elvio Fachinelli, Lea Melandri and Luisa Muraro, the article examines periodisations; the connections and divergences between anti-authoritarianism, psychoanalysis and feminism; gender and generational relations in the period between the “Long ’68” of the students’ and workers’ movement; the neo-feminism of groups and collectives; and the student and youth movement of 1977. Assuming the role of a laboratory for individual and collective experiments,—in dialogue with the vast area of the movements, but critical of party ideologies and the sectarianism of extra-parliamentary groups—the journal represents an important observatory of the desires, experiments and disappointments encountered by men and women in a dynamic, conflictual and violent urban context.